On outage secrecy minimisation in an energy harvesting relay assisted cognitive radio networks. Issue 18 (10th October 2018) - Banerjee, Avik; Maity, Santi P.; Roy, Subhabrata
Abstract : This work considers an energy harvesting (EH) based two‐hop relay assisted cognitive radio system that consists of a secondary transmitter, a relay node and a cooperative jammer operated in an underlay mode with a primary transmitter–receiver pair. An optimisation problem is formulated to minimise the secrecy outage probability under the constraints of simultaneously meeting the energy causality of the secondary transmit nodes, interference to the primary receiver and secondary outage probability. An analytical expression of the secrecy outage probability is developed followed by deriving the closed‐form expressions to determine the optimal transmit power of the source, the relay node and the fraction of the time slot for EH. Simulation results show that the minimum value of the secrecy outage probability is ∼ 6.4 % and ∼ 19.18 % less over the existing works.